Condición suficiente para la existencia de solución ´optima de un problema de programación cuadrática con cota simple - Chacon Barboza, Karol Tatiana (2023)
In the present work, the sufficient conditions are determined to guarantee the exis tence of the optimal solution of the quadratic programming problem with simple_x000D_ bound. To achieve the established objective, the tools of convex analysis have been_x000D_ used, and some important properties of the quadratic programming problem with_x000D_ simple bound have also been investigated. Consequently, it was determined and_x000D_ demonstrated that the strict convexity of the objective function of the quadratic_x000D_ programming problem with simple bounds is the sufficient condition to guarantee_x000D_ the existence of an optimal solution